What information do people want to know about hijamah? Informasi apa yang ingin diketahui orang tentang hijamah? - Rahmadi, Agus Rahmadi (Jurnal Kebidanan Midwiferia, 2017)
The purpouse of the reseaech is to explore community knowledge about cupping and identify the scope of information which is eiger to find out by community about cupping. This research uses qualitative method with phenomenological approach. The subjects of the research is the peoplewho have and have not cupping. Data collection was carried out through detail interviews using interview guidance. The research was conductedfrom May-June 2017 at PKM Tarumajaya, Clinic and RB Umi Rahma and Bekasi District Hospital. Sample is done by purposive sampling.The number of participants who get involved is 17 participants. Discussions in this study research include community knowledge,false views about cupping, cupping skepticism, and information which is eager to find out about cupping. These include the history of cupping,the edge of doing cupping, time for doing cupping, the point location of cupping, cupping indication, cupping contraindications, the equipment of cupping,the way of doing cupping, the procedure of cupping, the position of doing cupping, the weakness of cupping, the effects of cupping, the evaluationof cupping, the protection of cupping, the implemtentation of cupping, the security of cupping, formal implementation of cupping, cupping duringfasting, Cupping versus medical treatment, cupping versus traditional medicine. The lack of public knowledge about cupping tends to lead tothe stigmatization of cupping. It is advised to the government to make special rules of cupping and for service providers cupping in order tobetter promote cupping as a safe alternative treatment to the community.